Inference of a causal relation between low-density lipoprotein cholesterol and hypertension using mendelian randomization analysis - Tae-Hwa Go; Kyeong Im Kwak; Ji-Yun Jang; Minheui Yu; Hye Sim Kim; Jang Young Kim; Sang Baek Koh; Dae Ryong Kang (BMC, 2021)
Abstract Background It is known in some studies that higher the LDL-C, the greater the risk of developing cardiovascular disease. However, studies of the causal effects between LDL-C and hypertension are limited by their observational study design, and genetic epidemiology studies of associations between LDL-C and hypertension are lacking, as are studies using data for Koreans. In this study, we confirmed the causal effect of LDL-C on hypertension using Korean chip data. Method The epidemiology and genotype data were collected from the Korean Genome and Epidemiology Study conducted by the Korea National Institute of Health and covered 20,701 subjects. Single-nucleotide polymorphisms associated with LDL-C were selected (p-value < 5 × 10− 8) from the Global Lipids Genetics Consortium database, and Mendelian randomization analysis (MRA) was performed with counted genetic risk scores and weighted genetic risk scores (WGRSs) for 24 single-nucleotide polymorphisms. Result The assumptions for MRA were statistically confirmed, and WGRSs showed a strong association with LDL-C. Interestingly, while the relationship between LDL-C and hypertension was not statistically significant in the observational study, MRA study demonstrated that the risk of hypertension increased as LDL-C increased in both men and women. Conclusions The results of this study confirmed that the relationship between LDL-C and hypertension is greatly influenced by genetic information.